A Critical Approach to the UNESCO Principle “Scientific Knowledge and Integrity in Decision Making” in the Face of Climate Change: Contribution of Andean Indigenous Knowledge - Sakiko Yamaguchi; Junior Adolfo Villantoy Huaman; Celia Yanira Flores; Julián Berrocal Flores; Doris Castillo Gamboa (Canadian Journal of Bioethics)
“Scientific knowledge and integrity in decision-making” as presented in the UNESCO Declaration of Ethical Principles Article 7 may neglect existing local and traditional knowledge systems of indigenous communities. To address epistemic injustice towards the indigenous knowledge in climate change adaptation, it is important to engage with indigenous communities as equal members of society and learn from their relational and holistic understanding of nature.